La rappresentazione del potere cortigiano nel Marescalco di Pietro Aretino - Polegato, Andrea (Incontri. Rivista europea di studi italiani, 2013)
Representation of Courtly Power in the Marescalco of Pietro Aretino This article addresses a particular form of power, courtly power, displayed by Pietro Aretino in his play Il Marescalco (the Stablemaster). Aretino’s perspective is particularly interesting because he is probably the only intellectual in fifteenth- and sixteenth-century Italy who managed to emancipate himself from any political influences. From this privileged position, Aretino’s play describes the relationship between the monarch and his courtiers and the real nature of the legitimization of power. Indeed, the character of the Duke of Mantua never appears on stage despite his role in organizing the prank against the protagonist, the Stablemaster. In this way, the audience’s focus is mainly on the courtiers and their zeal in carrying out the Duke’s orders. Aretino also chooses to set his play in the center of the city of Mantua rather than in the Court. The twofold absence of the Duke and the Court on stage underscores the real nature of courtly power. According to Aretino, its legitimacy lies primarily in the courtiers’ passive attitude towards their ruler and in their attempts to favor him rather than in his direct intervention. Furthermore, while power is generally seen as a purely masculine domain, Aretino turns this idea upside-down in a very original way, by describing the passive attitude of the courtiers towards their master as a homosexual intercourse and the courtiers themselves as woman-haters.